Memahami Ketiadaan Kerja Sama Antar-Regional dalam Tata Kelola Perbatasan yang Terdesentralisasi: Bukti dari Indonesia–Timor Leste - Egidius Fkun; Magdalena Sunarty Pareira; Mariano Sengkoen (Interdisciplinary International Journal of Conservation and Culture, 2026)
Regional egocentrism has emerged as an unintended consequence of decentralization policies that grant local governments extensive authority. In this context, inter-regional cooperation becomes essential to facilitate the sharing of resources, benefits, and development responsibilities. However, such cooperation remains absent in several border areas, including the Indonesia–Timor Leste border regions of North Central Timor (TTU), Belu, and Malaka Regencies. This study aims to identify the factors underlying the absence of inter-regional cooperation in these regions. This research employs a qualitative exploratory approach. Data were collected through in-depth interviews and focus group discussions (FGDs) with purposively selected local government officials, non-governmental organizations, community leaders, and academics. Data were analyzed using an interactive model and validated through triangulation techniques. The findings reveal that the absence of cooperation is influenced by several factors, including limited understanding, lack of willingness, low interest, limited capacity, perceived lack of necessity, weak regulatory supervision, and the suboptimal role of the governor as the central government’s representative. These findings highlight the need for stronger institutional support and governance mechanisms to initiate and sustain inter-regional cooperation in decentralized border contexts.